Biological Monitoring of Human Exposure to Neonicotinoids Using Urine Samples, and Neonicotinoid Excretion Kinetics - Harada, Kouji H.; Tanaka, Keiko; Sakamoto, Hiroko; Imanaka, Mie; Niisoe, Tamon; Hitomi, Toshiaki; Kobayashi, Hatasu; Okuda, Hiroko; Inoue, Sumiko; Kusakawa, Koichi; Oshima, Masayo; Watanabe, Kiyohiko; et al. (PLOS ONE, 2016)
Background Neonicotinoids, which are novel pesticides, have entered into usage around the world because they are selectively toxic to arthropods and relatively non-toxic to vertebrates. It has been suggested that several neonicotinoids cause neurodevelopmental toxicity in mammals. The aim was to establish the relationship between oral intake and urinary excretion of neonicotinoids by humans to facilitate biological monitoring, and to estimate dietary neonicotinoid intakes by Japanese adults. Methodology/Principal Findings Deuterium-labeled neonicotinoid (acetamiprid, clothianidin, dinotefuran, and imidacloprid) microdoses were orally ingested by nine healthy adults, and 24 h pooled urine samples were collected for 4 consecutive days after dosing. The excretion kinetics were modeled using one- and two-compartment models, then validated in a non-deuterium-labeled neonicotinoid microdose study involving 12 healthy adults. Increased urinary concentrations of labeled neonicotinoids were observed after dosing. Clothianidin was recovered unchanged within 3 days, and most dinotefuran was recovered unchanged within 1 day. Around 10% of the imidacloprid dose was excreted unchanged. Most of the acetamiprid was metabolized to desmethyl-acetamiprid. Spot urine samples from 373 Japanese adults were analyzed for neonicotinoids, and daily intakes were estimated. The estimated average daily intake of these neonicotinoids was 0.53–3.66 μg/day. The highest intake of any of the neonicotinoids in the study population was 64.5 μg/day for dinotefuran, and this was <1% of the acceptable daily intake.